THE GENDER RELEVANCE OF COMPARATIVE PHRASEOLOGICAL NOMINATIONS OF A HUMAN BEING IN THE ENGLISH LANGUAGE PICTURE OF THE WORLD - Bylytsia, U. Ya. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2020)
The article deals with the gender analysis of the semantics of comparative phraseological units which denote the representatives of male and female sexes in the English language picture of the world. The article highlights the forms and levels of expressing the gender marking of the units under the study, outlines positive and negative gender stereotypes which are ascribed to women and men by the English society with the help of the means of comparative phraseology. The work raises the problem of the sources, where reference images originate from for their future gender stereotyping in the semantics of comparative phraseological units.